index 1b2ee6a..d44f824 100644 (file)
@@ -1,31 +1,43 @@
+<!--
+I would like to propose one pedegogical suggestion (due to Ken), which
+is to separate peg addition from non-determinacy by explicitly adding
+a "Let" construction to GSV's logic, i.e., "Let of var * term *
+clause", whose interpretation adds a peg, assigns var to it, sets the
+value to the value computed by term, and evaluates the clause with the
+new peg in place.  This can be added easily, especially since you have
+supplied a procedure that handles the main essence of the
+construction.  Once the Let is in place, adding the existential is
+purely dealing with nondeterminism.
+-->
+
+*      How shall we handle \[[&exist;x]]? As we said, GS&V really tell us how to interpret \[[&exist;xPx]], but for our purposes, what they say about this can be broken naturally into two pieces, such that we represent the update of our starting set `u` with \[[&exist;xPx]] as:

-*      How shall we handle \[[&exist;x]]? As we said, GS&V really tell us how to interpret \[[&exist;xPx]], but what they say about this breaks naturally into two pieces, such that we can represent the update of our starting set `u` with \[[&exist;xPx]] as:
-
-       <pre><code>u >>=<sub>set</sub> \[[&exist;x]] >>=<sub>set</sub> \[[Px]]
+       <pre><code>u >>= \[[&exist;x]] >>= \[[Px]]
</code></pre>

+       (Extra credit: how does the discussion on pp. 25-29 of GS&V bear on the possibility of this simplification?)
+
What does \[[&exist;x]] need to be here? Here's what they say, on the top of p. 13:

>       Suppose an information state `s` is updated with the sentence &exist;xPx. Possibilities in `s` in which no entity has the property P will be eliminated.

-       We can defer that to a later step, where we do `... >>= \[[Px]]`.
+       We can defer that to a later step, where we do `... >>= \[[Px]]`. GS&V continue:

-       >       The referent system of the remaining possibilities will be extended with a new peg, which is associated with `x`. And for each old possibility `i` in `s`, there will be just as many extensions `i[x/d]` in the new state `s'` and there are entities `d` which in the possible world of `i` have the property P.
+       >       The referent system of the remaining possibilities will be extended with a new peg, which is associated with `x`. And for each old possibility `i` in `s`, there will be just as many extensions `i[x/d]` in the new state `s'` as there are entities `d` which in the possible world of `i` have the property P.

Deferring the "property P" part, this corresponds to:

<pre><code>u updated with \[[&exist;x]] &equiv;
-               let extend_one = fun (one_dpm : bool dpm) ->
-                       List.map (fun d -> bind_dpm one_dpm (new_peg_and_assign 'x' d)) domain
-               in bind_set u extend_one
+               let extend one_dpm (d : entity) =
+                       dpm_bind one_dpm (new_peg_and_assign 'x' d)
+               in set_bind u (fun one_dpm -> List.map (fun d -> extend one_dpm d) domain)
</code></pre>

where `new_peg_and_assign` is the operation we defined in [hint 3](/hints/assignment_7_hint_3):

-               let new_peg_and_assign (var_to_bind : char) (d : entity) =
-                       (* we want to return not a function that we can bind to a bool dpm *)
-                       fun (truth_value : bool) : bool dpm ->
-                               fun ((r, h) : assignment * store) ->
+               let new_peg_and_assign (var_to_bind : char) (d : entity) : bool -> bool dpm =
+                       fun truth_value ->
+                               fun (r, h) ->
(* first we calculate an unused index *)
let new_index = List.length h
(* next we store d at h[new_index], which is at the very end of h *)
in let r' = fun var ->
if var = var_to_bind then new_index else r var
(* we pass through the same truth_value that we started with *)
-                                       in (truth_value, r', h')
+                                       in (truth_value, r', h');;

-       What's going on in this representation of `u` updated with \[[&exist;x]]? For each `bool dpm` in `u`, we collect `dpm`s that are the result of passing through their `bool`, but extending their input `(r, h)` by allocating a new peg for entity `d`, for each `d` in our whole domain of entities, and binding the variable `x` to the index of that peg.
-
-       A later step can then filter out all the `dpm`s according to which the entity `d` we did that with doesn't have property P.
+       What's going on in this proposed representation of \[[&exist;x]]? For each `bool dpm` in `u`, we collect `dpm`s that are the result of passing through their `bool`, but extending their input `(r, h)` by allocating a new peg for entity `d`, for each `d` in our whole domain of entities, and binding the variable `x` to the index of that peg. A later step can then filter out all the `dpm`s where the entity `d` we did that with doesn't have property P. (Again, consult GS&V pp. 25-9 for extra credit.)

-       So if we just call the function `extend_one` defined above \[[&exist;x]], then `u` updated with \[[&exist;x]] updated with \[[Px]] is just:
+       If we call the function `(fun one_dom -> List.map ...)` defined above \[[&exist;x]], then `u` updated with \[[&exist;x]] updated with \[[Px]] is just:

<pre><code>u >>= \[[&exist;x]] >>= \[[Px]]
</code></pre>

or, being explicit about which "bind" operation we're representing here with `>>=`, that is:

-       <pre><code>bind_set (bind_set u \[[&exist;x]]) \[[Px]]
+       <pre><code>set_bind (set_bind u \[[&exist;x]]) \[[Px]]
</code></pre>

-*      Let's compare this to what \[[&exist;xPx]] would look like on a non-dynamic semantics, for example, where we use a simple reader monad to implement variable binding. Reminding ourselves, we'd be working in a framework like this. (Here we implement environments or assignments as functions from variables to entities, instead of as lists of pairs of variables and entities. An assignment `r` here is what `fun c -> List.assoc c r` would have been in [week6](
+*      Let's compare this to what \[[&exist;xPx]] would look like on a non-dynamic semantics, for example, where we use a simple Reader monad to implement variable binding. Reminding ourselves, we'd be working in a framework like this. (Here we implement environments or assignments as functions from variables to entities, instead of as lists of pairs of variables and entities. An assignment `r` here is what `fun c -> List.assoc c r` would have been in [week7](

type assignment = char -> entity;;
type 'a reader = assignment -> 'a;;

-               let unit_reader (x : 'a) = fun r -> x;;
+               let reader_unit (value : 'a) : 'a reader = fun r -> value;;

-               let bind_reader (u : 'a reader) (f : 'a -> 'b reader) =
+               let reader_bind (u : 'a reader) (f : 'a -> 'b reader) : 'b reader =
fun r ->
let a = u r
in let u' = f a
in u' r;;

-               let getx = fun r -> r 'x';;
+       Here the type of a sentential clause is:
+
+               type clause = bool reader;;
+
+       Here are meanings for singular terms and predicates:
+
+               let getx : entity reader = fun r -> r 'x';;
+
+               type lifted_unary = entity reader -> bool reader;;

-               let lift (predicate : entity -> bool) =
+               let lift (predicate : entity -> bool) : lifted_unary =
fun r ->
let obj = entity_reader r
-                                       in unit_reader (predicate obj)
+                                       in reader_unit (predicate obj)

-       `lift predicate` converts a function of type `entity -> bool` into one of type `entity reader -> bool reader`. The meaning of \[[Qx]] would then be:
+       The meaning of \[[Qx]] would then be:

<pre><code>\[[Q]] &equiv; lift q
-       \[[x]] & equiv; getx
+       \[[x]] &equiv; getx
\[[Qx]] &equiv; \[[Q]] \[[x]] &equiv;
fun r ->
let obj = getx r
-                       in unit_reader (q obj)
+                       in reader_unit (q obj)
</code></pre>

Recall also how we defined \[[lambda x]], or as [we called it before](/reader_monad_for_variable_binding), \\[[who(x)]]:

-               let shift (var_to_bind : char) entity_reader (v : 'a reader) =
-               fun (r : assignment) ->
-                       let new_value = entity_reader r
-                       (* remember here we're implementing assignments as functions rather than as lists of pairs *)
-                       in let r' = fun var -> if var = var_to_bind then new_value else r var
-                       in v r'
+               let shift (var_to_bind : char) (clause : clause) : lifted_unary =
+                       fun entity_reader ->
+                               fun r ->
+                                       let new_value = entity_reader r
+                                       (* remember here we're implementing assignments as functions rather than as lists of pairs *)
+                                       in let r' = fun var -> if var = var_to_bind then new_value else r var
+                                       in clause r'

Now, how would we implement quantifiers in this setting? I'll assume we have a function `exists` of type `(entity -> bool) -> bool`. That is, it accepts a predicate as argument and returns `true` if any element in the domain satisfies that predicate. We could implement the reader-monad version of that like this:

-               fun (lifted_predicate : entity reader -> bool reader) : bool reader ->
-                       fun r -> exists (fun (obj : entity) -> lifted_predicate (unit_reader obj) r)
+               fun (lifted_predicate : lifted_unary) ->
+                       fun r -> exists (fun (obj : entity) ->
+                               lifted_predicate (reader_unit obj) r)

That would be the meaning of \[[&exist;]], which we'd use like this:

-       <pre><code>\[[&exist;]] \[[Q]]
+       <pre><code>\[[&exist;]] ( \[[Q]] )
</code></pre>

or this:

If we wanted to compose \[[&exist;]] with \[[lambda x]], we'd get:

-               let shift var_to_bind entity_reader v =
-                       fun r ->
+               let shift var_to_bind clause =
+                       fun entity_reader r ->
let new_value = entity_reader r
in let r' = fun var -> if var = var_to_bind then new_value else r var
-                               in v r'
+                               in clause r'
in let lifted_exists =
fun lifted_predicate ->
-                               fun r -> exists (fun obj -> lifted_predicate (unit_reader obj) r)
-               in fun bool_reader -> lifted_exists (shift 'x' getx bool_reader)
+                               fun r -> exists (fun obj -> lifted_predicate (reader_unit obj) r)
+               in fun bool_reader -> lifted_exists (shift 'x' bool_reader)

which we can simplify to:

-               let shifted v =
-                       fun r ->
-                               let new_value = r 'x'
+       <!--
+               let shifted clause =
+                       fun entity_reader r ->
+                               let new_value = entity_reader r
in let r' = fun var -> if var = 'x' then new_value else r var
-                               in v r'
+                               in clause r'
in let lifted_exists =
fun lifted_predicate ->
-                               fun r -> exists (fun obj -> lifted_predicate (unit_reader obj) r)
+                               fun r -> exists (fun obj -> lifted_predicate (reader_unit obj) r)
in fun bool_reader -> lifted_exists (shifted bool_reader)

-       and simplifying further:
+               fun bool_reader ->
+                       let shifted' =
+                               fun entity_reader r ->
+                                       let new_value = entity_reader r
+                                       in let r' = fun var -> if var = 'x' then new_value else r var
+                                       in bool_reader r'
+                       in fun r -> exists (fun obj -> shifted' (reader_unit obj) r)

-                       let shifted v =
-                               fun r ->
-                                       let new_value = r 'x'
+                       let shifted'' r obj =
+                                       let new_value = (reader_unit obj) r
in let r' = fun var -> if var = 'x' then new_value else r var
-                                       in v r'
-                       let lifted_predicate = shifted bool_reader
-                       in fun r -> exists (fun obj -> lifted_predicate (unit_reader obj) r)
+                                       in bool_reader r'
+                       in fun r -> exists (fun obj -> shifted'' r obj)

-                       let lifted_predicate = fun r ->
-                                       let new_value = r 'x'
+                       let shifted'' r obj =
+                                       let new_value = obj
in let r' = fun var -> if var = 'x' then new_value else r var
-                       in fun r -> exists (fun obj -> lifted_predicate (unit_reader obj) r)
+                       in fun r -> exists (shifted'' r)
+       -->
+
+               fun bool_reader ->
+                       let shifted r new_value =
+                                       let r' = fun var -> if var = 'x' then new_value else r var
+                                       in bool_reader r'
+                       in fun r -> exists (shifted r)
+
+       This gives us a value for \[[&exist;x]], which we use like this:
+
+       <pre><code>\[[&exist;x]] ( \[[Qx]] )
+       </code></pre>
+
+       Contrast the way we use \[[&exist;x]] in GS&V's system. Here we don't have a function that takes \[[Qx]] as an argument. Instead we have a operation that gets bound in a discourse chain:
+
+       <pre><code>u >>= \[[&exist;x]] >>= \[[Qx]]
+       </code></pre>
+
+       The crucial difference in GS&V's system is that the distinctive effect of the \[[&exist;x]]---to allocate new pegs in the store and associate variable `x` with the objects stored there---doesn't last only while interpreting some clauses supplied as arguments to \[[&exist;x]]. Instead, it persists through the discourse, possibly affecting the interpretation of claims outside the logical scope of the quantifier. This is how we'll able to interpret claims like:
+
+       >       If &exist;x (man x and &exist;y y is wife of x) then (x kisses y).
+
+       See the discussion on pp. 24-5 of GS&V.
+

+*      Can you figure out how to handle \[[not &phi;]] and the other connectives? If not, here are some [more hints](/hints/assignment_7_hint_6). But try to get as far as you can on your own.

-*      Can you figure out how to handle \[[not &phi;]] on your own? If not, here are some [more hints](/hints/assignment_7_hint_6). But try to get as far as you can on your own.